Abundance of Metioche Vittalicollis ( Orthoptera:Gryllidae) and Natural Enemies in A Rice Agroecosystem as Influenced by Weed Species - Sri Karindah; Bagyo Yanuwiadi; Liliek Sulistyowati; Peter T. Green (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
Weeds in the rice fields impact the population of M. vittaticollis and several predators on rice habitat. A study was conducted during rainy season 2004-2005 and dry season 2005, which selective weeding and weed strips were applied. In selective weeding, Monochoria vaginalis, Fimbristylis miliacea, Cyperus iria, and Limnocharis flava were left, and made a weed strip at the periphery of rice plot which was consisted of those four species. Clean weeding as farmers usually do was also applied as a control treatment. Results showed that the presence of weed plant species in the earlier planting season of dry season 2005 tended to maintain the population of the predatory insects of rice pests, in particularly M. vittaticollis and Anaxipha longipennis. Population of Ophionea nigrofasciata, Paederus spp. and Micraspis inops were not different among the treatment plots during rainy season (2004-2005) and dry season (2005). The species number of predator and parasitoids seemed to increase slower in the clean weeded plot in comparing with the species number in selectively weeded or weeds strips plot at early planting season. Rice yield in the experimental plots were not significantly different. Some weeds in the rice fields may not have adverse effects on rice productivity. Keywords : generalist predator, weeding, predatory cricket